Analisis Budaya Kemiskinan (Culture of Poverty) dan Alternatif Intervensi Psikososial untuk Pengentasan Kemiskinan di Kabupaten Sorong - Muslim, Muh Azis; Hidayat, Kania Falahiatika; Amaruddin, Muhammad Fadlan (Jayapangus Press, 2025)
Sorong Regency, located in Southwest Papua Province, is among the regions facing a serious poverty problem, where the number of people living in poverty has decreased by only 350 over a span of seven years, despite at least IDR 739.8 billion being allocated to poverty alleviation efforts. While numerous studies have identified structural factors as contributing to persistent poverty, few have examined the cultural dimensions. This study aims to identify the cultural roots of poverty in Sorong Regency and to propose psychosocial intervention alternatives that have proven effective in generating sustainable poverty reduction outcomes. The research adopts a qualitative approach, employing in-depth interviews, focus group discussions (FGDs), and participatory observation techniques. Findings indicate that patterns of dependency, resignation to fate, and limited social motivation are key elements of the culture of poverty in Sorong Regency. It is recommended that psychosocial interventions be implemented in the form of life skills training and the development of aspirations, using a spiritual approach through the strengthened involvement of the Church.